Pengaruh Pemimpin Digital terhadap Implementasi Sistem Informasi Manajemen di Organisasi Tradisional - Ilham; Amzar Raja (TeIKa, 2025)
This study aims to analyze the influence of Digital Leadership (DL) on the successful implementation of Management Information Systems (MIS) in traditional organizations. Using a Systematic Literature Review (SLR) approach, this research identifies and synthesizes relevant empirical and theoretical studies from 2020 to 2025. The findings indicate that Digital Leaders play a crucial role in integrating technological, human, and cultural aspects to ensure effective MIS implementation. They act as transformational agents who establish strategic direction and vision, foster an adaptive organizational culture, and empower employees through communication and trust. The study highlights that job crafting behavior serves as a mediating variable linking digital leadership to MIS effectiveness, while traditional organizational culture acts as a negative moderating factor that may hinder employee adaptation. Therefore, the success of MIS implementation in traditional organizations depends not only on technological readiness but also on the ability of Digital Leaders to navigate cultural challenges, promote collaboration, and cultivate a digital mindset across all organizational levels.